Morphological and anatomical assessment of KDML 105 (Oryza sativa L. spp. indica) and its mutants induced by low-energy ion beam - Narumol Boonrueng (2018)
Thai jasmine rice KDML 105 is consumed around the world. BKOS, PKOS and TKOS are new cultivars produced from low-energy ion beam induction in KDML 105. The purpose of this study is to compare the morphology and anatomy between KDML 105 and the three new cultivars. Seeds of the four cultivars were germinated and grown in pots until flowering phase. The plants' organs were observed and the lengths of culms, ligules, leaves and panicles were measured. Leaf surface area was calculated and numbers of roots, spikelets and tillers were counted. BKOS and PKOS had significantly shorter culms than KDML 105 and TKOS. The largest leaf area was found in KDML 105 followed by TKOS, BKOS and PKOS, respectively. Numbers of roots and tillers in BKOS and TKOS were significantly fewer than those in KDML 105 and PKOS. The number of spikelets per plant in BKOS was the lowest among all cultivars. For anatomical comparison, cross sections of culms and roots were observed. All plants had a similar arrangement of tissues, but the number and size of cells were different. Furthermore, longitudinal sections of culms showed that the lengths of epidermal and parenchyma cells were directly related with the length of the culm. To compare the leaves, both stomata and epidermal cells were counted and the lengths of the guard cells were measured. The lengths of guard cells of BKOS and PKOS were shorter, but the stomatal density and the stomatal index were significantly greater than those of KDML 105. For TKOS, though the length of guard cells was shorter than that in KDML 105, the difference was not significant. However, the stomatal density and stomatal index were significantly higher than those in KDML 105. © 2013 China National Rice Research Institute.